The Relationship Between English Tiktok Video Engagement and Self Directed Vocabulary Learning Among EFL University Students - Syarifah Soraya; Yasmine Mumtaazah; Fitriyah Fitriyah; Najwa Amalia; Abdul Syahid (FKIP, Universitas Palangka Raya, 2026)
The increasing prevalence of short-form video platforms has expanded opportunities for informal English learning beyond traditional classroom settings. TikTok has garnered a lot of interest among these platforms because of its microlearning features and high student engagement levels; nevertheless, there is still no empirical data connecting TikTok engagement to independent vocabulary acquisition. The purpose of this study is to look at the connection between EFL university students' self-directed vocabulary learning and their involvement with English TikTok videos. 86 undergraduate EFL students from a state institution in Palangka Raya, Indonesia, participated in the study, which used a quantitative correlational design. Two validated tools were used to gather data: the Self-Directed Vocabulary Learning Scale, which evaluates goal-setting, self-monitoring, and self-evaluation, and the TikTok Video Engagement Scale, which measures behavioural, affective, and cognitive involvement. Descriptive statistics and Pearson's product-moment correlation analysis were used to analyse the data. Higher levels of involvement were linked to more autonomous vocabulary acquisition practices, according to the results, which showed substantial positive correlations between all aspects of TikTok engagement and self-directed vocabulary learning (r =.445–.674, p <.001). Self-monitoring and self-evaluation were most strongly correlated with affective and cognitive involvement. These results imply that watching English-language TikTok videos has a significant positive impact on pupils' self-directed vocabulary growth. The study provides pedagogical implications for using digital interaction to improve learner autonomy and vocabulary acquisition in higher education and indicates that TikTok can serve as an effective supplemental microlearning tool in EFL situations.